2016
DOI: 10.1136/bmjopen-2016-011952
|View full text |Cite
|
Sign up to set email alerts
|

Does integrated care reduce hospital activity for patients with chronic diseases? An umbrella review of systematic reviews

Abstract: ObjectiveTo summarise the evidence regarding the effectiveness of integrated care interventions in reducing hospital activity.DesignUmbrella review of systematic reviews and meta-analyses.SettingInterventions must have delivered care crossing the boundary between at least two health and/or social care settings.ParticipantsAdult patients with one or more chronic diseases.Data sourcesMEDLINE, Embase, ASSIA, PsycINFO, HMIC, CINAHL, Cochrane Library (HTA database, DARE, Cochrane Database of Systematic Reviews), EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(169 citation statements)
references
References 56 publications
5
162
0
2
Order By: Relevance
“…In another example, clinicians spent less time transferring patients to other hospitals after the hospital at home initiative reduced admission and length of stay for other patients. 76 We found only one study 104 about whether or not in-reach into hospitals ensures timely discharge of patients, but it was a SR. It found that transition from hospital to home was most effective when interventions to expedite it were initiated during the inpatient phase and continued post discharge.…”
Section: Planned Referral Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…In another example, clinicians spent less time transferring patients to other hospitals after the hospital at home initiative reduced admission and length of stay for other patients. 76 We found only one study 104 about whether or not in-reach into hospitals ensures timely discharge of patients, but it was a SR. It found that transition from hospital to home was most effective when interventions to expedite it were initiated during the inpatient phase and continued post discharge.…”
Section: Planned Referral Networkmentioning
confidence: 99%
“…Half of the SRs quantified the reductions, giving figures ranging from 25% to 43%. 104 In a quantitative study of PACT PCMH implementation by the US VHA, Nelson et al 106 found that greater continuity of care (i.e. all other providers all working with and communicating with patient's primary care provider) was associated with lower likelihood of hospitalisation and mortality.…”
Section: Causal Link 3:5 -Multidisciplinary Team Supports Voluntary Imentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of multi-disciplinary teams have also shown promising results, particularly for heart failure and COPD. (Damery et al, 2016) There is little evidence that the use of other integrated care interventions, including collaborative case management and specialist disease clinics, can lead to reduced admissions.…”
Section: The Role Of Hospital Doctorsmentioning
confidence: 99%